Extending the Life World: Phenomenological Triangulation Along Two Planes - Zlatev, Jordan; Mouratidou, Alexandra (Biosemiotics, 2024)
Phenomenology is often mistakenly understood as both introspectionist and anthropocentric and thus as incapable of providing us with objective knowledge. While clearly wrong, such critiques force us to spell out how the life world that is given in human experience is in fact not anthropocentric and not incompatible with science. In this article we address this by adapting a recent proposal to extend the key methodological principle of cognitive semiotics, phenomenological triangulation , along two planes. The first is horizontal and concerns the dimensions of Self, Others and Things, as irreducibly interrelated dimensions of the life world. The second is vertical, and deals with the way phenomena are accessed: from a first-person (philosophical), second-person (empirical in a qualitative sense) and third-person (scientific in a quantitative sense) perspective. With each perspective, the life world becomes correspondingly extended beyond direct experience. It is thus neither static nor confining. We exemplify each step with corresponding research, also providing examples of how non-human animals and not only human beings may serve as Others, thus addressing the critique of anthropocentrism. We conclude by pointing out how, despite some theoretical differences, the focus on subjectivity and the explicit or implicit adoption of the principle of phenomenological triangulation can serve as common ground for cognitive semiotics and biosemiotics.